The Kyrgyz Republic : Farm Mechanization and Agricultural Productivity - Guadagni, Maurizio (World Bank, Washington, DC and FAO, Rome, 2014)
This policy note reviewed the status of farm machinery in the Kyrgyz Republic. Agricultural productivity, particularly in terms of grain yields, is low because of underinvestment. This note finds that a significant deficit in agricultural machinery is hindering sector productivity. The Kyrgyz Republic has fewer tractors per hectare than any comparable country, with a deficit estimated at 40 percent. The deficit of combine harvesters, estimated at 45 percent, is even more critical. When the age of agricultural machinery is taken into account, the underinvestment becomes even more acute. The reduced domestic production of wheat exacerbates food security concerns. Inadequate access to credit and small farm size are the main factors that constrain farm mechanization. The policy note presents three sets of short- to medium-term policy options to: i) promote the demand for farm machinery, by developing credit lines for agricultural productive assets, leasing, facilitating access to secondhand equipment, and testing/demonstrating the efficiency of farm machinery for small-scale farming; ii) increase the supply of farm machinery, by facilitating the development of mechanical services contracting and improving access to farm machinery import markets, including for second-hand equipment; and iii) remove obstacles to private investment, by avoiding distributions of farm machinery or inputs in-kind, the setting of production targets for specific crops, and ensuring that the private sector is free to fulfill its role.